Pengaruh Pemberian Terapi White Noise Terhadap Penurunan Tingkat Nyeri Pada Pasien Post-Operasi Sectio Caesarea: The Effect of Providing White Noise Therapy on Reducing Pain Levels in Post-Caesarean Section Surgery Patients - Sonata, Gita Ria; Purnama, Agus; Koto, Yeni (Dohara POAJ, 2024)
Introduction: Pain felt by the patient (post-partum mother). If it is not managed well after a caesarean section it will have an impact on the length of time the body recovers after surgery difficulty in mobilizing and the bond between mother and baby will be disturbed or not fulfilled. The problem of pain felt by mothers after caesarean section surgery can be treated by providing therapy both pharmacologically and non-pharmacologically namely using white noise therapy. Methods: The design or type of research used in this is experimental research. Quasi-experimental Non-Equivalent Control Group or Non-Randomized Control Group Pre-test-Post-test Design. The population in this study was pre-operative caesarean section patients at Z General Hospital sampling used non-random sampling with purposive sampling technique with a total sample of 26 respondents. Results: Based on the research results, the average standard deviation of pain measurements in post-caesarean section patients from the analysis test results using the Wilcoxon-W test showed that p 0,001 < 0,05 with an effect size of 1,00; which means there is an effect of giving white noise therapy in reducing pain in post-operative caesarean section patients. Discussion: The pain felt by the patient after having a caesarean section at Hospital X in the Jagakarsa area before being given white noise therapy reached a moderate to severe pain scale. There was an effect before and after white noise therapy was given to the intervention group and there was a significant difference between the pain group and the control group after being given white noise therapy.